Initial Formulation of the Isha Prayer Time in the Book Al-Fiqh 'Alaa Madzahib Al-Arba'ah - Durrotun Nahdliah An Najiah; Ahmad Izzuddin; M Bathoni (Universitas Islam Negeri Mataram, 2026)
This study discusses the formulation of the beginning time of Isha prayer according to the four schools of Islamic jurisprudence, namely Hanafi, Maliki, Shafi'i, and Hanbali, as explained in the book Al-Fiqh 'ala al-Madzahib al-Arba'ah by Abdurrahman al-Jaziri. The main issue in this study lies in the different interpretations of the meaning of syafaq as the sign of the end of Maghrib prayer time and the beginning of Isha prayer time. This research uses a qualitative method with a library research approach, employing descriptive-comparative analysis techniques to compare the opinions of scholars and relate them to astronomical phenomena. The results show that the Hanafi school argues that the beginning of Isha time starts after the disappearance of syafaq abyadh (white twilight), while the Maliki, Shafi'i, and Hanbali schools argue that it begins after the disappearance of syafaq ahmar (red twilight). These differences are influenced by the interpretation of hadith, geographical conditions, astronomical observations, and the legal reasoning methods of each school. In the Indonesian context, the opinion of the majority scholars is more widely applied because it is more suitable for the geographical conditions of the equatorial region and serves as the basis for determining prayer schedules by the Ministry of Religious Affairs. This study shows that differences of opinion regarding the beginning of Isha prayer time are not contradictions, but rather a form of the richness of ijtihad in Islamic jurisprudence.